EDUKASI MANAJEMEN LUKA SEDERHANA DI RUMAH UNTUK MENCEGAH INFEKSI PADA MASYARAKAT - Iswanti Purwaningsih; Sumarti Endah Purnamaningsih Maria Margaretha; Laily Mualifah; Nur Cahya Rachmawati (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2024)
Minor wounds are common health problems in daily life and may lead to infection if not managed properly. In many communities, home-based wound care practices are still influenced by traditional habits and a lack of medically validated information. This community service program aimed to improve public knowledge regarding simple wound management at home as a preventive measure against infection. The activity was conducted in Mangir Kidul Hamlet, Sendangsari Village, Pajangan Subdistrict, Bantul Regency using a pre-experimental design with a one-group pre-test and post-test approach. A total of 30 adult participants were selected through purposive sampling. Health education was delivered through interactive lectures and demonstrations of simple wound care techniques. Data were collected using a structured questionnaire that had undergone content validity and reliability testing. The results showed an increase in the mean knowledge score from 56.3 in the pre-test to 82.7 in the post-test. Wilcoxon signed-rank test analysis indicated a statistically significant difference in knowledge scores before and after the educational intervention (p < 0.05). This program demonstrates that simple wound care education is effective in improving community knowledge and has the potential to reduce the risk of wound infection at the household level.